Gold incorporated mesoporous silica thin film model surface as a robust SERS and catalytically active substrate - Sekhar, Anandakumari Chandrasekharan Sunil; Vinod, Chathakudath Prabhakaran (Molecules, 2016)
Ultra-small gold nanoparticles incorporated in mesoporous silica thin films with accessible pore channels perpendicular to the substrate are prepared by a modified sol-gel method. The simple and easy spin coating technique is applied here to make homogeneous thin films. The surface characterization using FESEM shows crack-free films with a perpendicular pore arrangement. The applicability of these thin films as catalysts as well as a robust SERS active substrate for model catalysis study is tested. Compared to bare silica film our gold incorporated silica, GSM-23F gave an enhancement factor of 10(3) for RhB with a laser source 633 nm. The reduction reaction of p-nitrophenol with sodium borohydride from our thin films shows a decrease in peak intensity corresponding to -NO2 group as time proceeds, confirming the catalytic activity. Such model surfaces can potentially bridge the material gap between a real catalytic system and surface science studies.
Keywords: gold nanoparticles; model catalysis; SERS; Thin films